Lipid-phase transitions of the strictly anaerobic bacteria Veillonella parvula and Anaerovibrio lipolytica. - Verkley, A J (1975)
As a basis for physicochemical studies on the membranes of the strictly anaerobic bacteria Veillonella parvula, Anaerovibrio lipolytica, and Megasphaera elsdenii, the fatty acyl and alk-1-enyl moieties on the phosphoglycerides of these organism were characterized. Uncommon is the high proportion of a heptadecenoic acyl and alk-1-enyl moiety in these three lactate-fermenting bacteria. In contrast to V. parvula and A. lipolytica, M. elsdenii contains high amounts of branched-chain acyl and alk-1-enyl moieties. Freeze-etching electron microscopy showed that the lipids of the plasma membranes of V. parvula and A. lipolytica go from the liquid crystalline to the gel state upon lowering of the temperature, indicating that the membrane lipids are predominantly in the fluid state. No lipid-protein segregation could be detected in the plasma membrane of M. elsdenii. This can be explained by the abundance of branched-chain fatty acyl and alk-1-enyl residues in the membranes of this organism which may prevent lipid-protein segregation during the lipid-phase transition.